Early Screening of Hemoglobinopathy in Indonesia Using Erythrocyte Indices - Yenny Surjawan; Hwee Lian Tan; Rahajuningsih Dharma Setiabudy; Wiwik Rositawati (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: The mutation spectrums of hemoglobinopathy are different among populations that yield a different result of erythrocyte indices. Calculation of erythrocyte indices with some formula has been reported to differentiate between hemoglobinopathy and non-hemoglobinopathy, but its cut-off should be recalculated specific for each population to gain a better sensitivity and specificity. We aimed to evaluate red blood cell count (RBC), Mentzer index, red cell distribution width (RDW), RDW index (RDWI), Shine and Lal index (S&L) and Green and King index (G&K) to screen hemoglobinopathy in Indonesia.METHODS: A retrospective cross-sectional study was performed on 202 subjects. The diagnosis of hemoglobinopathy was determined based on the results of complete blood count (CBC) data, high-performance liquid chromatography (HPLC) and Hemoglobin H (HbH) inclusion body. The ferritin concentration was checked to determine the status of iron. The erythrocytes indices were analyzed and calculated to predict hemoglobinopathy. RESULTS: A total 202 subjects who met the criteria were involved in this study. Fifty percent showed pure hemoglobinopathy and 4% showed a combination of thalassemia and hemoglobinopathy. The hemoglobin concentration and RBC were significantly higher, and the mean corpuscular volume (MCV) and RDW were significantly lower in hemoglobinopathy compared to iron deficiency. The difference was not significant if the hemoglobinopathy was combined with iron deficiency. By this study's cut-off, the G&K and RDWI showed the highest accuracy, sensitivity, and specificity.CONCLUSION: The new cut-off of erythrocyte index and its calculation to screen hemoglobinopathy in Indonesia showed a higher sensitivity and specificity, especially for G&K and RDWI with cut-off 73 and 228, respectively. The presence of iron deficiency in hemoglobinopathy could decrease the sensitivity.KEYWORDS: hemoglobinopathy, RBC, Mentzer index, RDW, RDWI, S&L, G&K